Carbon Sequestration for Global-Scale Climate Change Mitigation: Overview of Strategies Plus Enhanced Roles for Perennial Crops - Denis J. Murphy (Crops)
Climatic changes threaten many forms of crop production as well as adversely affecting global ecosystems and human activities. There are two principal ways in which the balance of the global carbon cycle can be restored, firstly by decreasing anthropogenic CO2 emissions and secondly by increasing the rates of carbon sequestration. Even if emissions are successfully reduced to net zero over the coming decades, it will still be essential to reduce atmospheric CO2 concentrations to preindustrial levels. This can only be achieved by global-scale carbon sequestration of the order of gigatonnes (Gt) of CO2 annually. Over recent decades, engineering approaches have been proposed to tackle carbon sequestration. However, their technological effectiveness has yet to be demonstrated at a global scale, with even the most optimistic current values at less than 0.1 Gt CO2/yr, i.e., 50–100-fold less than required to meet IPCC targets for 2050. In contrast, biological carbon sequestration already operates as a proven global mechanism that also has the potential for increased effectiveness by harnessing high-yield tropical vegetation including perennial crops with sequestration values already exceeding 1 Gt CO2/yr. This review will contrast engineering and biological approaches to carbon sequestration with a particular focus on the potential for perennial crops, especially in the tropics. The major conclusions are that (i) the 2 Gt CO2/yr capacity of biological carbon sequestration already dwarfs that of all engineering approaches at 0.0013 Gt CO2/yr, (ii) biological sequestration is proven to operate at global scale, and (iii) compared to engineering approaches, it will be orders of magnitude less expensive to upscale further in the coming decades.